EFFECTIVE DIVERSITY MANAGEMENT INITIATIVES - Suat Begec (International Review of Management and Marketing, 2013)
Diversity characteristics defines into four areas; personality, internal and external characteristics, and organizational characteristics. Today it is hard to find individuals, organizational and management styles all similar to each other. Twenty-first century leaders face diversity challenges in many arenas and it is a fact that leaders have to live with these diversities. Values affects on the management and organization systems. The global values gain importance and remove the sources of diversities. The leaders believe that the values should be mostly protected. This article focuses on effective diversity management initiatives.